2020
DOI: 10.1016/j.heliyon.2020.e05006
|View full text |Cite
|
Sign up to set email alerts
|

Optimized platelet rich plasma releasate (O-rPRP) repairs galactosemia-induced ovarian follicular loss in rats by activating mTOR signaling and inhibiting apoptosis

Abstract: Platelet rich plasma contains a collection of growth factors, and an optimal formulation, named O-rPRP, contains the highest possible concentration of growth factors. Purpose Challenging the healing power of O-rPRP in a high-galactose diet-induced premature ovarian insufficiency (POI) experimental rat model. Methods Rats were divided into four groups of ten rats each and treated for four week as follows; 1) the control group, fed with normal diet and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Cyclophosphamide and cisplatin are commonly used in clinical practice, and becoming the most common method of establishing an animal model of POI. In addition, other recognized causes of POI include metabolism disorders, infections, toxins, and environmental factors ( Naleway et al, 2018 ; Moslehi et al, 2019 ; Rostami Dovom et al, 2019 ; El Bakly et al, 2020 ).…”
Section: The Pathogenesis Of Poi and The Application Of Stem Cell-der...mentioning
confidence: 99%
“…Cyclophosphamide and cisplatin are commonly used in clinical practice, and becoming the most common method of establishing an animal model of POI. In addition, other recognized causes of POI include metabolism disorders, infections, toxins, and environmental factors ( Naleway et al, 2018 ; Moslehi et al, 2019 ; Rostami Dovom et al, 2019 ; El Bakly et al, 2020 ).…”
Section: The Pathogenesis Of Poi and The Application Of Stem Cell-der...mentioning
confidence: 99%
“…Moreover, Balakrishnan et al (2016) showed that GalT KO fibroblasts had downregulated PI3K/AKT signaling and decreases in the IGF-1 receptor. Lastly, it has been proposed that galactose-induced stress activates the expression of the micro-RNA miR-223 ( El Bakly et al , 2020 ), which could then impede cell proliferation, partly by targeting the IGF-1 receptor and inhibiting its downstream PI3K/AKT pathway ( Jia et al , 2011 ; Pan et al , 2014 ).…”
Section: Onset and Mechanism Of Damage Including Potential Signaling ...mentioning
confidence: 99%
“…Currently, mRNA therapies are being investigated at the preclinical stage for the disease and might be promising treatment options to store defective proteins 87,[89][90][91] . Rescuing GALT activity with pharmacological chaperones has also been proposed as a potential therapeutic option 92 .…”
Section: Part Iii: Exploring New Treatment Options For Cgmentioning
confidence: 99%
“…receptor. Lastly, it has been proposed that galactose-induced stress activates the expression of the micro-RNA miR-223 89 , which could then impede cell proliferation, partly by targeting the IGF-1 receptor and inhibiting its downstream PI3K/AKT pathway 71,73 .…”
mentioning
confidence: 99%